Population Variation and Interrelationships between Laccase Enzyme Activity and Oil Percentage of Jatropha curces L. - Kumar, R.V.; Tripathi, Yogendra K.; Yadav, V. P.; Ahlawat, S.P.; Handa, A.K.; ., Ajit (Indian Journal of Agroforestry, 2020)
Forty accessions of Jatropha curcas L. were analyzed for their ability to produce laccase enzyme and on the basis of laccase activities, polymorphism of Jatropha curcas L. was also studied at the genetic level. Among forty accessions, NRCJ-32 produced (368.99) higher activities of laccase whereas NRCJ-48 (247.48) showed low production of this enzyme. The difference observed in the enzyme activities between accessions was found to be adequate for analyzing the extent of genetic variability at the intra-specific level. The analysis revealed that there was highest genetic identity between NRCJ-32 vs. NRCJ-48 (271. 8%) whereas lowest (2.00%) genetic identity was observed between NRCJ-54 vs. NRCJ-43. Further these activities were correlated with oil percentage of Jatropha curcas accessions. Results Â indicated that the accession, which had higher activity of laccase enzyme activity, showed higher oil percentage. The information generated will help in getting adequate basis about growth and development pattern of Jatropha curcas L. in terms of enhancement of oil yield and its components.Â